Hypogonadism Secondary to Hyperprolactinaemia: Successful Treatment but Adverse Consequences - Narayanan, R. P.; Bujawansa, S.; Qureshi, Z.; Rimmer, M.; Heald, A. (Experimental and Clinical Endocrinology & Diabetes, 2012)
It is accepted that care must be taken in initiating testosterone replacement in hypogonadal individuals with historically low androgen levels. However less is reported about the influence of restoration of normal endogenous testosterone production on behaviour.Here we report how the adverse sequelae of successful treatment of hypogonadism secondary to hyperprolactinaemia, manifesting as irritability and low threshold to aggression, were managed through a joint approach between psychiatrist and physician.
Keywords: macroprolactinoma; testosterone; libido